Mental Illness Among Women Attending A National Mental Health Referral Center in Kenya: Unpacking Predisposing Factors and Interventions - Godfrey Mayoka; Rechael Nyaboke Getange; Linus Makokha Wafula; Allan Korir; Daisy Chonge; Sharon Mumbua; David Olpengs (Masters Program in Public Health, 2024)
Background: Mental illness is an escalating global public health menace that affects women disproportionately. This study aimed to assess the prevalence and factors contributing to mental illness among Kenyan women alongside the interventions explored to manage the conditions.Subjects and Method: This was a mixed-method study comprising retrospective case series analysis of 285 inpatient records of women seeking mental health services at a national referral center in Nairobi, Kenya, and key informant interviews involving mental health service providers, from January 2022 to June 2022. The Variables of this study were sociodemographic data. Information was collected on socioeconomic factors, mental illness profiles, and mental illness interventions. Data analysis was performed using SPSS version 23 and thematic analysis.Results: Bipolar mood disorder (42%), schizophrenia (33%), and psychosis (25%) were the most prevalent mental conditions. While strained relationships (38%), financial challenges (35%), death of a loved one (29%), and substance abuse (27%) frequently contributed to mental illness, psychotherapy, and psychoeducation were pivotal in patient management. Poor government funding hindered in-service training initiatives as well as training and recruitment of community health workers, contributing to the unavailability of free counseling services. Despite these hurdles, the hospital explored alternative means to ensure access to mental healthcare including offering admission fees waivers, implementing repatriation programs, and subsidizing the costs of medications for psychotic patients.Conclusion: This study highlights the complex factors affecting women’s mental health in Kenya and rallies for increased support towards holistic mental healthcare interventions for this vulnerable population. Improving mental health literacy to reduce stigma associated with mental illness, and addressing financial, as well as hospital-related administrative barriers, can enhance access to mental health care.